MENGEMBALIKAN FUNGSI FAQIH DAN ULAMA? DALAM PEMIKIRAN WILAYAT-I FAQIH KHOMEINI SEBAGAI MODEL ULAMA? SYI?AH PASCA REVOLUSI IRAN - Anwar, Saeful; Shidiq, Agus Sholahudin (At-Tuhfah : Jurnal Studi Keislaman, 2021)
This article discusses the concept of the Al-Faqih Region offered by Khomeini during the Iranian revolution on February 11th 1979, as an ideal form in restoring the role of the faqih to hold power and as a Shia political system and its implementation in state leadership amid world politics. Khomeini explicitly said that the priests are obliged to guide the people after the death of the Prophet Muhammad, the priests have the character of ma'shum. Wilayat-i Faqih articulated Imam Khomeini's essential ideas about the state and its aims. This concept is a normative principle that these powers (or functions) should not be delegated to the same person to prevent abuse of power by the parties involved power. Likewise, the Wilayat-i Faqih concept developed by Imam Khomeini divides the power of implementing Islamic governance into three state institutions, namely the executive, legislative, and judicial institutions. The executive and judicial powers are in the hands of the faqih who carry out the function as representatives of the priests, so the legislative power is entirely the right of God. However, according to Khomeini in the concept of Wilayat-i Faqih, only the faqih holds the highest authority, all power comes from his position as the highest mujtahid who has the greatest authority in interpreting legal sources.